(3egGQGJ GdGJUGd ddEYdGejjf h GdJQHhjjf h GdOYGI (B/s - (3MLGH, eMeO efjQs ((3GdbGgQI (B:s (3OGQ GdaLQ ddfTQ h GdJhRjY ,s, 2000)
(3Gf GdgOa ef gPG GdcJGH gh eSGYOJc Ydi JMSf NHQGJc h egGQGJc GdGJUGdjI Gj RjGOI bOQGJc Ydi GdJCKjQ aj GdGNQjfs
Keywords: (3egGQGJ GdEJUGds; (3GdEJUGds